2013
DOI: 10.1371/journal.pone.0077011
|View full text |Cite
|
Sign up to set email alerts
|

High Cryptic Diversity across the Global Range of the Migratory Planktonic Copepods Pleuromamma piseki and P. gracilis

Abstract: Although holoplankton are ocean drifters and exhibit high dispersal potential, a number of studies on single species are finding highly divergent genetic clades. These cryptic species complexes are important to discover and describe, as identification of common marine species is fundamental to understanding ecosystem dynamics. Here we investigate the global diversity within Pleuromamma piseki and P. gracilis, two dominant members of the migratory zooplankton assemblage in subtropical and tropical waters worldw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 78 publications
4
24
0
Order By: Relevance
“…2B), but typically, three to eight times more rDNA OTUs were found than described morphospecies in the best-known lineages within these categories. This is within the range of the number of cryptic species typically detected in globally-distributed pelagic taxa using molecular data (28,29). The general congruency between genetic and morphological data in the cataloged compartment of eukaryotic plankton suggests that the protocols used, from plankton sampling to DNA sequencing, recovered the known eukaryotic biodiversity without major qualitative or quantitative biases.…”
Section: A Global Metabarcoding Approachmentioning
confidence: 57%
“…2B), but typically, three to eight times more rDNA OTUs were found than described morphospecies in the best-known lineages within these categories. This is within the range of the number of cryptic species typically detected in globally-distributed pelagic taxa using molecular data (28,29). The general congruency between genetic and morphological data in the cataloged compartment of eukaryotic plankton suggests that the protocols used, from plankton sampling to DNA sequencing, recovered the known eukaryotic biodiversity without major qualitative or quantitative biases.…”
Section: A Global Metabarcoding Approachmentioning
confidence: 57%
“…Consequently, for organisms for which no recent taxonomic revision is available, the sampling scheme should both follow the requirements of population biology and phylogenetic systematics. Only a widespread sampling of a supposedly cosmopolitan species may reveal several diverging lineages restricted to isolated areas or distinct habitats as exemplified by the study of the supposedly ubiquitous and widespread amphipod Eurythenes gryllus (Lichtenstein in Mandt, 1822) (Havermans et al 2013) or the copepods Pleuromamma piseki Farran, 1929, and Pleuromamma gracilis Claus, 1863 (Halbert et al 2013). Collecting in undersampled or unexplored areas may also reveal new divergent lineages.…”
Section: T a X O N O M I C F O U N D A T I O N S O F C O N N E C T I mentioning
confidence: 99%
“…Thus, it has 36 been assumed that allopatric speciation may be less important in pelagic species than 37 sympatric or parapatric speciation (Norris, 2000). During the past years molecular studies 38 have revealed that many supposedly widespread species are mosaics of several cryptic or 39 pseudocryptic species (Andrews et al, 2014; Burridge et al, 2015; Cornils and Held, 2014; 40 Darling et al, 2007;Halbert et al, 2013; Hunt et al, 2010;Miyamoto et al, 2012). The mode …”
Section: Introduction 34mentioning
confidence: 99%